Mechanisms driving an unusual latitudinal diversity gradient for grasses. Issue 1 (4th October 2013) - Visser, Vernon; Clayton, W. Derek; Simpson, David A.; Freckleton, Robert P.; Osborne, Colin P.
Abstract Aim For most higher‐order taxa, species diversity peaks sharply in the moist tropics and declines rapidly at higher latitudes. However, the mechanisms driving this latitudinal gradient are numerous, remain uncertain and are even undocumented in some important major clades such as the grasses. Grasses are a cosmopolitan, important plant family with more than 11, 000 species world‐wide. Our aims were: to investigate the latitudinal distributions of species richness for different grass lineages, and the grass family as a whole; and to test hypotheses proposed in general for the latitudinal diversity gradient or specifically as determinants of grass species richness patterns at the global scale. Location Global. Methods We used the most comprehensive global database of grass distributions currently available to calculate species richness for 340 political regions of the world. Using generalized additive models we used these data to model the latitudinal gradients of species richness for different grass lineages and for the grass family as a whole. We constructed multiple regression models to include climatic, productivity, topographic, habitat and geographic variables. Results An unusual, shallow latitudinal diversity gradient arises because different grass lineages exhibit contrasting latitudinal patterns. This reflects differential specialization of grass lineages to arid and cool environments, the legacy of historical effects, most notably the Gondwanan origin of the grasses, and a strong association between grasses and topographically heterogeneous, mountainous regions. Main conclusions The grasses are one of the relatively few higher‐order lineages that exhibits an atypical latitudinal gradient; this has arisen because of climatic specialization of particular grass lineages to cold and arid environments. Key additional roles have been inferred for historical biogeography and topographical heterogeneity in determining global patterns of grass species richness. These mechanisms have generally been under‐appreciated and are probably important for many other lineages.